Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Produktivitas Kinerja Karyawan pada PT. Chiara Allegra Living - Faisal Alif Ashar; Mukhamad Kholil Aswan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of work environment and work discipline on employee performance productivity at PT. Chiara Allegra Living. A comfortable and conducive work environment and work discipline in complying with company regulations play an important role in increasing employee performance productivity. The research method used is a quantitative descriptive approach. The sample was taken using simple random sampling technique, resulting in 60 respondents with data obtained through questionnaire distribution and analyzed using multiple linear regression technique to test the relationship between independent variables (work environment and work discipline) and dependent variables (employee performance productivity). The results of the study using SPSS software have a Cronbach's Alpha value above 0.60 indicating that each research variable is interdependent and consistent. After conducting a reliability test, then conducting a normality test shows that the Asymp. Sig (2-tailed) value is 0.051, which is higher than 0.05. The Kolmogorov-Smirnov (K-S) test shows that the research residuals have a normal distribution. The results of the regression test show that simultaneously the work environment and work discipline had a positive and significant effect on employee productivity, with an R value of 0.617 and an R square of 0.381, meaning that 38.1% of the variation in employee productivity could be explained by these two variables. Partially, work discipline has the most dominant influence with a regression coefficient of 0.593 followed by work environment with 0.152. These findings indicate that company management needs to improve the quality of the work environment and maintain work discipline. With this strategy, companies can increase employee performance productivity and ultimately have a positive impact on future employee performance.